The art of landscape detail : fundamentals, practices, and case studies - Kirkwood, Niall. 4 0 16; 5 (New York : John Wiley & Sons, 1999)
A holistic approach to landscape detail in the landscape design process that examines research approaches, discusses such issues as materials, climate, and durability, and presents in-depth case studies of eight award-winning projects.
Includes bibliographical references (p. 333-346) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Landscape architecture; 20; 2